Comparative Evaluation of the Presence of Insertion Enthesophyte in the Achilles Tendon by X-Ray and Magnetic Resonance Imaging: Intra and Inter Observer Reliability. Issue 4 (22nd October 2020) - Baumfeld, Tiago S.; Silva, Thiago A.; Benevides, Wilel A.; Silveira, Dário M.; Baumfeld, Daniel
Category: Other; Sports Introduction/Purpose: To evaluate the intra and interobserver variation on the presence of enthesophyte in patients with Achilles insertional tendinopathy and the clinical radiological correlation of x-ray (X-ray) and magnetic resonance images (MRI). Methods: We selected Lateral X-ray images of the calcaneus and videos of ankle MRI in which we showed the entire thickness of the calcaneus in the coronal, sagittal and axial views, in both T1 and T2 weightings, of 20 patients with Achilles insertional tendinopathy. 5 foot and ankle surgeons and 5 musculoskeletal radiologists, with varied experience time, analysed the images. Intra and Interobserver correlations were studied with the kappa index. Results: The average Ƙ intraobserver of the results of the MRI analyzes was 0.49, and the average Ƙ interobserver of the results of the MRI analyzes was 0.47. The mean Ƙ intraobserver values of the results of the X-ray analyzes were 0.61, while the Ƙ interobserver had a value of 0.60. We also observed that the group of less experienced surgeons and radiologists showed a worse Ƙ intraobserver than the more experienced ones. Conclusion: The values are in agreement with previous studies, confirming moderate intraobserver and interobserver reproducibility in MRI exams and good or substantial interobserver and interobserver reliability in X-ray exams.